2006
DOI: 10.1016/s1477-3880(15)30118-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Curriculum Choice at A-level: Why is Business Studies More Popular than Economics?

Abstract: This paper uses A-level Information System (ALIS) data to quantify the determinants of the choice between Economics and Business Studies at A-level. These subjects are often perceived as close curriculum options and possible substitutes in the UK. Subject choice is modelled using an underlying latent variable approach. On the basis of a series of counterfactual exercises an overall average grade differential, a measure of their comparative difficulty, is estimated to be 1.3 (old) UCAS points, equivalent to app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Between 1992 and 2000, the number of students taking economics in England fell by over 50%, while the number taking business studies increased by over 80% (Bachan 2004). Several researchers have examined why economics has become less popular as an A-level subject, and they have come to similar conclusions (Ashworth and Evans 2000;Ashworth and Evans 2001;Reilly and Bachan 2002;Bachan 2004;Bachan and Barrow 2006).…”
Section: The Context -Choosing A-level Subjectsmentioning
confidence: 93%
See 1 more Smart Citation
“…Between 1992 and 2000, the number of students taking economics in England fell by over 50%, while the number taking business studies increased by over 80% (Bachan 2004). Several researchers have examined why economics has become less popular as an A-level subject, and they have come to similar conclusions (Ashworth and Evans 2000;Ashworth and Evans 2001;Reilly and Bachan 2002;Bachan 2004;Bachan and Barrow 2006).…”
Section: The Context -Choosing A-level Subjectsmentioning
confidence: 93%
“…Of the three subjects being considered in this study, economics attracts the smallest proportion of female candidates across the UK (DCSF 2009). Ashworth and Evans (2000) state that the perceived abstract and/or mathematical nature of economics is off-putting particularly to girls, while Bachan and Barrow (2006) found that females are more likely to believe that they will not find the subject interesting and enjoyable. A comparison is made between male and female achievement in accounting, business studies and economics over the four-year period of this study.…”
Section: Relative Difficulty Of Different Subjectsmentioning
confidence: 99%
“…For example, between 1992 and 2004, the number of students taking economics in England fell by 62 per cent while the number taking business studies over the same period increased by 70 per cent (Bachan and Barrow 2006). However, the number of students taking economics at A level in 2009 increased by 15.2 per cent from the previous year (DCSF 2010).…”
Section: Vocationalisation Of the School Curriculummentioning
confidence: 98%
“…There is consensus in the literature about which Alevel subjects are easier or more difficult, and business studies is always categorised as being easier (Fitz-Gibbon and Vincent 1994;Alton and Pearson 1996;Dearing 1996;Bachan and Barrow 2006). However, these studies did not distinguish between the applied business and traditional, 'academic' business studies A levels.…”
Section: Vocationalisation Of the School Curriculummentioning
confidence: 99%
“…They also reported that these differences have been stable over time. Given that high grades are more difficult to achieve in Economics than Business Studies there has been an incentive for students to prefer Business Studies (Bachan and Barrow 2006).…”
Section: Advanced Level Subject Difficulty and Individual Choicementioning
confidence: 99%